Auris - System for Facilitating the Musical Perception for the Hearing Impaired - Araújo, Felipe Alves; Batista, Carlos Eduardo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2016: Proceedings of the 22nd Brazilian Symposium on Multimedia and the Web, 2016)
The Auris system aims to improve music perception for deaf people. The system includes a set of tools for audio conversion into a new media (consisting of audio filtered synchronized with tactile impulses) to be played through loud speakers and special haptic interfaces, an improvement in musical experimentation by deaf people. The rating system is performed through the use of EEG interfaces, from the analysis of the recorded signals during cognitive testing. This article includes the presentation of the Auris system architecture and the results of its first stages of evaluation.